Erythritol as a Next-Generation Sweetener: properties, metabolism, cardiovascular risk and gut health implications – A literature review - Julia Skowrońska-Borsuk; Martyna Narożniak; Adrianna Ewa Pękacka; Bartłomiej Czerwiec; Adam Borsuk; Joanna Katarzyna Pergoł; Malwina Wojtas; Julia Borkowska; Zuzanna Krupa; Julia Sposób (Quality in Sport, 2025)
Introduction and Purpose: